DESIGN OF AN IOT-BASED SMART IRRIGATION SYSTEM USING SOIL MOISTURE SENSORS FOR WATER EFFICIENCY - Aisyah, Nurul; Ulhaq, Early Dia; Dharmawan, Aldi; Purbakawaca, Rady (Prodi Fisika FST UNJA, 2025)
Water scarcity and inefficient irrigation practices remain key challenges in agriculture. This study aims to design and evaluate an IoT-based smart drip irrigation system controlled by an ESP32 microcontroller for optimizing water use. The system integrates a calibrated YL-69 soil moisture sensor and DHT21 temperature-humidity sensor for real-time environmental monitoring, with control and data visualization provided via the Blynk platform. Experimental results demonstrated that the system effectively maintained soil moisture within the optimal range of 30 – 50%. The developed system achieved irrigation efficiency between 90 – 95% and reduced total water consumption by approximately 40% compared to conventional methods. The results showed that integrating soil moisture sensors within an IoT-based control framework can significantly enhance water efficiency.